Plasticidade fenotípica de linhagens de arroz de terras altas - Inácio, Hermínio Bento (2016)
Assessing genotypes to be recommended in different environments is a step that requires a long time and resources. This assessment is extremely important especially when breeding objectives are selecting genotypes with high homeostasis, adaptability associated with high production and stability. The objectives of this researcher were to study the phenotypic plasticity of upland rice lines for the production parameter in multiple environments. The experiments were conducted in nine different environments matching the combination of place and agricultural years. 13 elite lines from UFLA, EPAMIG and EMBRAPA rice and beans were tested. Data were analysed using the statistical package SISVAR by individual analysis and subsequently conducting joint analysis. Using the package by means of three methods Wricke, Annicchiarico, and Lin Binns was verified the adaptability and stability. The Annicchiarico Lin and Binns methods were similar in the identification of four adaptive and stable lines: CMG 2097 CMG 1896 CMG 2089, 2085. The Wricke method did not identified any genotype as stable and all achieved the same behaviour in various environments.